An integrated assembly method for realizing low interfacial impedance of solid-state lithium battery by using in-situ polymerization gel electrolyte

CN122950604APending Publication Date: 2026-10-20DONGGUAN FENGCHI ELECTRIC SWITCH NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611074446.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,这一路线存在根本性缺陷:聚合完成后,凝胶电解质中仍保留大量未聚合的碳酸酯或醚类溶剂分子,这些自由溶剂分子在高于4.2伏的正极电位下发生持续氧化分解,同时在低电位负极侧发生还原分解,在电极-凝胶界面上逐渐积累一层高阻抗的有机-无机复合钝化层

Benefits of technology

1.本发明通过将碳酸亚乙烯酯作为活性稀释剂和牺牲成膜组分引入可聚合前驱体体系,并采用阶梯升温原位聚合程序,使碳酸亚乙烯酯在第一升温阶段的主体聚合中优先保留为未聚合小分子,在第二升温阶段向电极活性材料颗粒表面富集并参与界面交联,形成化学组成从颗粒表面向凝胶本体方向连续渐变的界面修饰层。该界面修饰层消除了凝胶电解质与电极活性材料之间离子传输机制的突变界面,从物理结构层面降低了界面阻抗的产生来源。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_8
    Figure SMS_8
  • Figure SMS_11
    Figure SMS_11
Patent Text Reader

Abstract

This invention discloses a method for achieving integrated assembly of solid-state lithium batteries with low interfacial impedance using in-situ polymerized gel electrolyte, belonging to the field of electrochemical energy storage device manufacturing technology. The method involves mixing polymerizable ionic liquid monomers, crosslinking agents, lithium salts, thermal initiators, and vinylene carbonate to form a permeation treatment solution. This solution is then used to impregnate porous positive and negative electrodes, followed by step-heating in-situ polymerization: In the first heating stage at 65°C, a primary gel is formed, with vinylene carbonate preferentially retained in a small molecular state; in the second heating stage at 85°C, vinylene carbonate is enriched on the surface of the electrode active material particles and undergoes interfacial crosslinking, forming an interface modification layer with continuously varying components; in the third heating stage at 100°C, the residual monomer is converted, resulting in an integrated composite electrode. This invention eliminates interfacial impedance from both physical structure and chemical composition perspectives, achieving low initial interfacial impedance and excellent cycle stability in solid-state lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage device manufacturing technology, and in particular to an integrated assembly method for achieving low interfacial impedance of solid-state lithium batteries using in-situ polymerized gel electrolyte. Background Technology

[0002] Solid-state lithium batteries use non-flammable solid electrolytes instead of liquid organic electrolytes, fundamentally solving the safety hazards of liquid lithium-ion batteries. However, the solid-solid interface problem between the solid electrolyte and the electrode active materials remains a core bottleneck restricting its practical application. This interface problem manifests itself in three interrelated aspects.

[0003] The first level is the degradation of interfacial physical contact. During charging and discharging, the positive and negative active materials undergo volume changes of 3% to 6% and up to more than 100%, respectively. Due to the lack of fluidity, the solid electrolyte gradually separates from the initial point contact with the active material particles under cyclic stress, forming voids and cracks, which leads to the breakage of ion transport paths and a sharp increase in the battery's internal resistance.

[0004] The second level is the interfacial space charge layer effect. At the interface between the inorganic solid electrolyte and the oxide cathode, due to the electrochemical potential difference, lithium ions spontaneously migrate to form a depletion layer. Its ionic conductivity is several orders of magnitude lower than that of the bulk electrolyte, becoming the rate-controlling step of the interfacial charge transfer kinetics.

[0005] The third aspect is the accumulation of interfacial by-reaction products. When some inorganic solid electrolytes with high ionic conductivity come into contact with high-voltage positive electrodes or lithium metal negative electrodes, interfacial redox reactions occur due to insufficient electrochemical windows, generating ionicly insulating interfacial phases that continuously consume active materials and increase interfacial resistance.

[0006] To alleviate the aforementioned problems, in-situ polymerization of gel electrolytes has been extensively studied. This route involves injecting a liquid precursor containing polymerizable monomers, crosslinking agents, and lithium salts into the assembled battery cell. The liquid precursor thoroughly wets the porous structure of the electrode, initiating polymerization and forming a conformally coated gel electrolyte layer, partially transforming the solid-solid interface into a gel-solid interface. However, this route has a fundamental drawback: after polymerization, a large number of unpolymerized carbonate or ether solvent molecules remain in the gel electrolyte. These free solvent molecules undergo continuous oxidative decomposition at positive electrode potentials above 4.2 V, and simultaneously reductive decomposition at lower negative electrode potentials, gradually accumulating a high-resistivity organic-inorganic composite passivation layer at the electrode-gel interface. The chemical composition and thickness of this passivation layer continuously evolve with cycling, leading to a continuous increase in interfacial impedance. Furthermore, a significant heterojunction interface exists between this passivation layer and the gel electrolyte bulk and electrode surface, where the ion transport mechanism abruptly changes, thus constituting a source of interfacial impedance.

[0007] Therefore, there is an urgent need for an integrated assembly method that can suppress interfacial chemical side reactions between the gel electrolyte and the electrode active material under working voltage and eliminate heterojunction interfacial structures, while ensuring sufficient initial interfacial contact. Summary of the Invention

[0008] To achieve the above objectives, the present invention provides an integrated assembly method for realizing low interfacial impedance of solid-state lithium batteries using in-situ polymerized gel electrolyte, comprising:

[0009] The beneficial effects of this invention are: 1. This invention introduces vinylene carbonate as an active diluent and sacrificial film-forming component into a polymerizable precursor system, and employs a stepped-temperature in-situ polymerization procedure. This allows vinylene carbonate to preferentially remain as an unpolymerized small molecule during the bulk polymerization in the first heating stage, and then accumulate on the surface of the electrode active material particles and participate in interfacial crosslinking during the second heating stage, forming an interfacial modification layer with a continuously gradient chemical composition from the particle surface towards the gel bulk. This interfacial modification layer eliminates the abrupt interface of the ion transport mechanism between the gel electrolyte and the electrode active material, reducing the source of interfacial impedance at the physical structural level.

[0010] 2. The side of the interface modification layer adjacent to the electrode active material particles is rich in vinylene carbonate derivatives. It is electrochemically inert within the normal operating voltage range of the battery, effectively isolating the migratable components in the gel electrolyte from direct contact with the electrode surface, preventing oxidation side reactions at high potentials and reduction side reactions at low potentials, and inhibiting the continuous increase of interfacial impedance during charge-discharge cycles from a chemical compositional perspective.

[0011] 3. This invention uses identical polymerizable precursor solutions and polymerization processes to prepare the positive and negative composite electrodes, respectively. During stacking and assembly, uniform pressure is applied to induce interdiffusion, physical entanglement, and local covalent cross-linking of polymer segments in the homogeneous gel electrolyte layers on both sides, fusing them into a single gel electrolyte with continuous ion transport. This eliminates the macroscopic physical interfacial impedance between the positive and negative electrode electrolytes in traditional stacking processes. This homogeneous fusion effect, combined with the component gradient effect of the aforementioned interface modification layer, synergistically enhances the solid-state lithium battery, achieving both low initial interfacial impedance and high stability of interfacial impedance under long-cycle conditions. Attached Figure Description

[0012] To more clearly illustrate the technical solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, those skilled in the art can obtain other drawings based on these drawings without creative effort.

[0013] Figure 1This is a flowchart of the steps of the method of the present invention. Detailed Implementation

[0014] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. It should also be noted that, to make the embodiments more comprehensive, the following embodiments are the best and preferred embodiments, and those skilled in the art can use other alternative methods to implement some well-known technologies; moreover, the accompanying drawings are only for more specific description of the embodiments and are not intended to specifically limit the present invention.

[0015] Please see Figure 1 To make the technical solution, operational details and beneficial effects of the present invention clearer, the following is a detailed description through terminology explanation, method principle description and specific embodiments.

[0016] In this invention, a "polymerizable ionic liquid monomer" refers to a compound whose chemical structure simultaneously contains olefin bonds capable of participating in free radical polymerization and a cationic-anionic combination characteristic of ionic liquids. A preferred monomer is 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide salt, with 1-vinyl-3-ethylimidazolium as the cation and bis(trifluoromethanesulfonyl)imide as the anion. This monomer provides an ionicly conductive microenvironment while constructing a polymer network through the participation of vinyl groups in polymerization.

[0017] "Crosslinking agents containing at least two olefin bonds" refers to compounds containing two or more carbon-carbon double bonds per molecule that can participate in free radical polymerization. Preferred is polyethylene glycol diacrylate, with a number average molecular weight in the range of 200 to 1000, more preferably 400 to 800. The crosslinking agent forms chemical crosslinking points during polymerization, imparting the required mechanical properties and dimensional stability to the gel electrolyte.

[0018] "Thermal initiator" refers to a compound that decomposes under heating conditions to generate free radicals, thereby initiating olefin polymerization. Azobisisobutyronitrile (AIBN) is preferred. ABObisisobutyronitrile has a half-life of approximately 10 hours at 65°C, which shortens significantly at 85°C, and its thermal decomposition behavior matches the step-heating program.

[0019] "Ethylene carbonate," acting as an active diluent and sacrificial film-forming component, is mixed with the polymerizable precursor solution in step 3. Its function is twofold: reducing the overall viscosity of the permeation treatment solution to promote deep penetration into the porous structure of the electrode; and preferentially participating in interfacial crosslinking reactions on the surface of the electrode active material particles during the subsequent step-heating stage to form an interfacial modification layer.

[0020] "Step-by-step in-situ polymerization treatment" refers to heating in stages according to a preset heating rate and isothermal plateau, instead of using a single isothermal polymerization condition. The first heating stage involves raising the temperature from 25°C to 65°C at a rate of 1°C / min and holding it at that temperature. The main purpose is to initiate the bulk copolymerization of the polymerizable ionic liquid monomer and crosslinking agent, forming a nascent gel electrolyte network within the electrode pores. At this stage, due to the steric hindrance of its cyclic structure and its slightly lower free radical polymerization activity compared to acrylate and vinyl monomers, the polymerization conversion rate of vinylene carbonate at 65°C is much lower than that of the bulk monomer. Most of the vinylene carbonate is uniformly dispersed in the nascent gel electrolyte as unpolymerized small molecules. The second heating stage involves raising the temperature from 65°C to 85°C at a rate of 0.5°C / min and holding it at that temperature. At this point, the bulk polymerization is nearing completion, and the system viscosity increases significantly. Under the combined effects of confined pore space, concentration gradient, and surface energy difference, unpolymerized vinylene carbonate molecules accumulate in the vicinity of the electrode active material particles and participate in interfacial crosslinking and grafting reactions on the particle surface, forming an interfacial modification layer rich in vinylene carbonate-derived components. This interfacial modification layer is connected to the already formed gel electrolyte network through covalent grafting and physical entanglement, without a clear phase separation interface. In the third heating stage, the temperature is increased from 85℃ to 100℃ at a rate of 0.5℃ / min and held at a constant temperature to allow the remaining unreacted monomers in the system to complete their final transformation, eliminate migratable small molecules, and stabilize the structure of the interfacial modification layer.

[0021] The "interface modification layer" refers to a nanoscale thin layer formed in situ on the surface of the electrode active material particles, with a chemical composition distinct from the gel electrolyte bulk. The thickness of the interface modification layer ranges from 3 nm to 30 nm. The chemical composition characteristics of the interface modification layer are as follows: using X-ray photoelectron spectroscopy combined with argon ion etching for depth profiling, layer-by-layer analysis from the particle surface towards the gel bulk shows a gradual decrease in the intensity of the C 1s characteristic signal of vinylene carbonate (corresponding to carbon in the carbonate group), while the intensity of the N 1s characteristic signal of the ionic liquid monomer (corresponding to imidazolium cation) gradually increases. By normalizing and comparing the intensity-etching time curves of these two signals, it can be determined that the compositional transition region between the interface modification layer and the gel bulk is a continuous gradual change, rather than a step-like abrupt change. The etching rate calibration was performed using a standard sample of thermally oxidized silica of known thickness etched under the same conditions. Due to the difference in etching rates between organic gels and silica, the above thickness conversion values ​​are approximate. The actual interface modification layer thickness is mainly based on direct observation results from transmission electron microscopy, with X-ray photoelectron spectroscopy depth profiling used to verify the gradual change trend of the composition. Angle-resolved X-ray photoelectron spectroscopy (ARPS) was used as an auxiliary characterization technique to detect chemical information at different depths by varying the photoelectron emission angle, further verifying the existence of a compositional gradient. Transmission electron microscopy was used to assist in observing the morphology and thickness range of the interface modification layer. Samples were prepared using frozen ultrathin sections to preserve the original structure of the gel electrolyte.

[0022] "Integrated positive electrode composite electrode" and "integrated negative electrode composite electrode" refer to composite structures in which the pores of a positive electrode porous electrode or a negative electrode porous electrode are completely filled with gel electrolyte, and the gel electrolyte has formed the interface modification layer on the surface of the electrode active material particles. The electrode and electrolyte are integrated into one in terms of structure and ion transport path.

[0023] "Continuous whole" refers to the formation of a continuous ion-conducting phase region at the contact interface of the gel electrolyte layers on both sides after the positive and negative composite electrodes are stacked and pressurized. This is achieved through molecular-scale segmental diffusion, physical entanglement, and further reactions of residual unreacted alkene bonds. Electrochemical impedance spectroscopy (EIS) tests show that the ion transport impedance of the fused region is on the same order of magnitude as that of the bulk gel electrolyte, with no additional impedance arc caused by the macroscopic interface. To avoid ambiguity, the term "continuous whole" does not mean that the region is absolutely homogeneous at the atomic scale, but rather that, relative to the physical interface formed by the mechanical contact of two independent film layers in traditional stacked assembly, the composition and ion transport properties at the interface of this invention exhibit a smooth spatial transition.

[0024] Test method description: Porosity determination: The true density method is adopted. First, the true density of the electrode active material powder, conductive additive powder and binder is determined by a helium hydrometer. The theoretical true density of the electrode coating is calculated according to the formula weighting. Then, the dry weight of the electrode sheet is weighed and the thickness and area of ​​the electrode sheet are measured to calculate the apparent volume. The ratio of apparent density to theoretical true density is converted into solid volume fraction. Porosity is equal to 1 minus solid volume fraction.

[0025] Permeation treatment solution filling rate determination: The weighing method was used. First, the mass of the dry electrode sheet before impregnation was weighed. After impregnation and dripping off the surface liquid, the mass of the wet electrode sheet is weighed. The mass of the infiltrated permeation treatment solution is Based on the apparent volume of the electrode and measured porosity Calculate the total pore volume Density of the permeate treatment solution The specific gravity bottle method was used to measure the filling rate at 25℃. The filling rate F was calculated using the following formula:

[0026] Residual monomer content determination: Gas chromatography was used. A gel electrolyte sample was scraped from the integrated composite electrode, accurately weighed, dissolved in acetonitrile, and ultrasonically extracted for 2 hours. The supernatant was collected by centrifugation, and n-octane was added as an internal standard for gas chromatography analysis. A polyethylene glycol capillary column and a flame ionization detector were used. The contents of residual vinylene carbonate and residual 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide salt were calculated as a percentage of sample mass and determined using the standard curve method.

[0027] Ionic conductivity determination: The gel electrolyte was sandwiched between two stainless steel blocking electrodes, and the electrochemical impedance spectroscopy was measured. The real intercept in the high-frequency region of the Nyquist plot was taken as the bulk resistance. ionic conductivity Calculated by the following formula:

[0028] Where d is the thickness of the gel electrolyte membrane, and A is the electrode area. The measurement temperature is 25℃.

[0029] Storage modulus determination: Using a parallel plate rheometer, the integrated positive electrode composite electrode or the integrated negative electrode composite electrode was cut into circular pieces with a diameter of 8 mm. Dynamic frequency scanning was performed at 25℃ with a strain amplitude of 0.1% and a frequency range of 0.1 Hz to 10 Hz. The storage modulus G' at 1 Hz was taken as the storage modulus value of the gel electrolyte.

[0030] Interfacial impedance measurement and growth rate calculation: Electrochemical impedance spectroscopy of solid-state lithium batteries was measured at 25℃, with a frequency range of 1 MHz to 0.01 Hz and an AC perturbation voltage amplitude of 5 mV. An equivalent circuit model was used. Perform a fitting, where is the ohmic resistance. and Representing the interfacial impedance between the gel electrolyte and the electrode, and the constant phase angle element, respectively. Let represent charge transfer impedance and double-layer capacitance, and W represent diffusion impedance. ZView is used as the fitting software. is taken as the interface impedance. The interface impedance growth rate after the nth cycle is defined as:

[0031] in This is the initial interface impedance before the cycle begins.

[0032] X-ray photoelectron spectroscopy depth profiling: A monochromatic Al Kα source was used, with an analysis region diameter of 100 μm. The argon ion etching gun voltage was 1 kV, and the etching region was 2 mm × 2 mm. The etching rate was calibrated under the same conditions using a thermally oxidized silica standard sample, approximately 0.1 nm / s. C 1s, N 1s, O 1s, F 1s, and S 2p spectra were acquired. Peak confinement of the C 1s spectrum was based on reference spectra of pure vinylene carbonate polymerization products and pure 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide salt polymerization products. The peak near 290.5 eV was attributed to carbonate-based carbons, the peak near 286.5 eV to ether / alcohol-based carbons, and the peak at 284.8 eV to aliphatic or contaminating carbons. The criterion for the end of the interface modification layer / the beginning of the gel bulk was that the N 1s signal intensity reached 95% of its bulk stable value.

[0033] Example 1 Step 1: Prepare the positive porous electrode.

[0034] Lithium nickel cobalt manganese oxide positive electrode active material powder, conductive carbon black, and polyvinylidene fluoride binder were weighed at a mass ratio of 94:3:3. First, the polyvinylidene fluoride binder was dissolved in N-methylpyrrolidone to form a transparent solution. Then, conductive carbon black was added for pre-dispersion, and finally, the positive electrode active material powder was added. The mixture was stirred for 5 hours in a vacuum planetary mixer at a revolution speed of 20 rpm and a rotation speed of 1000 rpm to obtain a uniform positive electrode slurry. This positive electrode slurry was coated onto one side of a 15 μm thick aluminum foil current collector using a slot extrusion coating machine, with the coating thickness controlled to be 120 μm. The coated electrode was placed in a forced-air drying oven and dried at 100℃ for 12 hours to obtain a porous positive electrode. After drying, the electrode was compacted once using a two-roll press at room temperature and a linear pressure of 0.5 t / cm. According to the porosity determination method described above, the porosity of the compacted porous positive electrode was measured to be 35%.

[0035] Step 2: Prepare the negative porous electrode.

[0036] Artificial graphite anode active material powder, conductive carbon black, and composite aqueous binder were weighed at a mass ratio of 95:2:3. The composite aqueous binder was prepared by pre-mixing styrene-butadiene rubber and sodium carboxymethyl cellulose in deionized water at a mass ratio of 2.5:1 to form an emulsion with a solid content of 15%. The composite aqueous binder emulsion and part of the deionized water were added to a mixing tank, conductive carbon black was added for pre-dispersion, then artificial graphite powder was added, and the remaining deionized water was added to make the slurry solid content 45%. The mixture was stirred for 5 hours in a vacuum planetary mixer at a revolution speed of 20 rpm and a rotation speed of 1000 rpm to obtain a uniform anode slurry. The anode slurry was coated on one side of a 10 μm thick copper foil current collector using a slot extrusion coating machine, with the coating thickness controlled to be 100 μm. The coated electrode was placed in a forced-air drying oven and dried at 90℃ for 12 hours to obtain a porous anode electrode. After drying, the electrode sheet was compacted once using a two-roll press at room temperature and a linear pressure of 0.4 t / cm. Based on the porosity determination method described above, the porosity of the compacted negative electrode was measured to be 40%.

[0037] Step 3: Prepare polymerizable precursor solution.

[0038] The operation was carried out in a glove box under an inert gas atmosphere, with a water content of 0.05 ppm and an oxygen content of 0.05 ppm. 1-Vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide salt, polyethylene glycol diacrylate (number average molecular weight 600, measured value 612), lithium bis(trifluoromethanesulfonyl)imide, and azobisisobutyronitrile were weighed out in a molar ratio of 100:4:25:1.5 and added to a sealed glass bottle. The solution was magnetically stirred at 25°C for 3 hours to obtain a homogeneous, transparent, polymerizable precursor solution.

[0039] Step 4: Prepare the permeation treatment solution.

[0040] Under the same glove box atmosphere conditions as in step 3, the polymerizable precursor solution prepared in step 3 was mixed with vinylene carbonate at a volume ratio of 7:1, and magnetically stirred at 25°C for 0.8 hours to obtain a homogeneous permeation treatment solution. The measured density of the permeation treatment solution at 25°C was 1.42 g / cm³. 3 .

[0041] Step 5: Introduce the permeation treatment solution into the electrode pores.

[0042] Under the same glovebox atmosphere as in step 3, the positive porous electrode prepared in step 1 was cut into 55 mm × 55 mm pieces, and the negative porous electrode prepared in step 2 was cut into 57 mm × 57 mm pieces. The cut positive and negative porous electrodes were completely immersed in the permeation treatment solution prepared in step 4, ensuring the solution completely submerged the electrodes. The temperature of the permeation treatment solution was maintained at 30°C during immersion. After immersion for 60 minutes, the electrodes were removed using PTFE tweezers and suspended in a sealed glass container. They were left to stand for 8 minutes to allow excess permeation treatment solution to drip off naturally, resulting in positive and negative porous electrodes with permeation treatment solution adsorbed on them. Using the same filling rate determination method as described above, the filling rate of the permeation treatment solution in the positive porous electrode was measured to be 96%, and the filling rate in the negative porous electrode was 97%.

[0043] Step 6: Step-heat in-situ polymerization treatment.

[0044] The positive and negative porous electrodes, each containing the permeation treatment solution, were placed separately in sealed stainless steel containers equipped with pressure gauges and inlet / outlet valves. After sealing, the container was evacuated to -0.08 MPa and then refilled with high-purity argon until the gauge pressure reached 0.08 MPa. This process was repeated three times to maintain an argon atmosphere with a gauge pressure of 0.08 MPa inside the container. The container was then placed in a programmable temperature oven, and the following heating program was executed: First heating stage: Increase the temperature from 25℃ to 65℃ at a heating rate of 1℃ / min, and maintain the temperature at 65℃ for 2 hours; The second heating stage: the temperature is increased from 65℃ to 85℃ at a heating rate of 0.5℃ / min, and then kept at 85℃ for 4 hours. The third heating stage: the temperature is increased from 85℃ to 100℃ at a heating rate of 0.5℃ / min, and then kept at 100℃ for 2 hours.

[0045] Then stop heating, open the oven door and let the container cool down naturally at room temperature. After the container temperature drops to 25°C, remove the electrode to obtain an integrated positive electrode composite electrode and an integrated negative electrode composite electrode.

[0046] The resulting integrated positive electrode composite was characterized. Transmission electron microscopy (TEM) samples were prepared using cryogenic ultrathin sections. The interface region between the positive electrode active material particles and the gel electrolyte was observed under TEM. An interface modification layer with contrast between the particles and the gel bulk was observed on the particle surface, with a thickness ranging from 8 nm to 15 nm measured in multiple fields of view. X-ray photoelectron spectroscopy depth profiling was used to acquire spectra at 0, 30, 60, 120, 240, and 480 seconds during argon ion etching. The endpoint of the interface modification layer was defined as the N 1s peak intensity reaching 95% of the bulk stable value, corresponding to an etching time of 150 seconds. Based on a calibrated etching rate of 0.1 nm / s, the thickness of the interface modification layer was approximately 15 nm. Analyzing the C 1s spectra at each etching time point, the area fraction of the carbonate-based carbon peak (approximately 290.5 eV) attributed to vinylene carbonate gradually decreased from 18% at 0 seconds to 3% at 150 seconds. Simultaneously, the N 1s signal intensity attributed to the ionic liquid monomer gradually increased from 30% of the bulk intensity at 0 seconds to 95% of the bulk intensity at 150 seconds. The two signal intensity-etching depth curves showed smooth changes without obvious inflection points or steps, indicating that the chemical composition of the interface modification layer underwent a continuous and gradual transition.

[0047] According to the above method for determining the residual monomer content, the content of residual vinylene carbonate monomer in the integrated positive electrode composite electrode was found to be 0.3 wt%, and the content of residual 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide salt was found to be 0.6 wt%. According to the above method for determining ionic conductivity, the ionic conductivity of the gel electrolyte was determined to be... S / cm. Following the above method for determining storage modulus, the storage modulus G' at 1 Hz was taken as 0.5 MPa. The glass transition temperature of the gel electrolyte was determined to be -55℃ by differential scanning calorimetry.

[0048] Step 7: Stacking, assembly, and packaging.

[0049] Under the same glove box atmosphere conditions as in step 3, the integrated positive electrode composite electrode obtained in step 6 was cut into 50 mm × 50 mm dimensions, and the integrated negative electrode composite electrode was cut into 52 mm × 52 mm dimensions. The gel electrolyte surfaces of the positive and negative electrodes were stacked face-to-face in a flat platen clamp, and a uniform pressure of 0.1 MPa was applied and maintained for 60 seconds. The stack was then removed, placed into an aluminum-plastic composite film punch, and thermo-sealed in a vacuum sealing machine at a vacuum level of -0.09 MPa to obtain a single-cell solid-state lithium battery. The nominal capacity of this battery is 80 mAh.

[0050] Comparative Example 1 The difference from Example 1 is that vinylene carbonate is not added when preparing the permeation treatment solution in step 4. The permeation treatment solution consists only of the polymerizable precursor solution prepared in step 3. The operations of steps 1 to 3 and steps 5 to 7 are exactly the same as in Example 1. Because vinylene carbonate is not added, the viscosity of the permeation treatment solution is relatively high. In step 5, the immersion time is extended to 90 minutes to achieve a similar degree of pore filling. The positive electrode filling rate was measured to be 95%, and the negative electrode filling rate was 96%. Step 6 uses the same stepped heating and closed container operation, but because there is no vinylene carbonate present, there is no enrichment of vinylene carbonate and interfacial film formation process in the second heating stage.

[0051] Comparative Example 2 The difference from Example 1 is that step 6 does not use a stepped heating process, but instead uses a single isothermal polymerization. The positive and negative porous electrodes, both containing the permeation treatment solution, are placed in a sealed container and purged with argon gas to 0.08 MPa. The container is then placed in an oven and heated from 25°C to 80°C at a rate of 2°C / min, held at 80°C for 8 hours, and then allowed to cool naturally. All other steps are the same as in Example 1.

[0052] Comparative Example 3 The difference from Example 1 is that the integrated positive and negative composite electrodes use polymerizable precursor solutions with different formulations. The positive electrode side uses the same polymerizable precursor solution and subsequent operations as in step 3 of Example 1. When preparing the polymerizable precursor solution for the negative electrode side, vinylene carbonate is not used, and the amount of the crosslinking agent polyethylene glycol diacrylate is doubled, i.e., the molar ratio of 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide salt, polyethylene glycol diacrylate, lithium bis(trifluoromethanesulfonyl)imide, and azobisisobutyronitrile is 100:8:25:1.5; the negative electrode side permeation treatment solution consists only of this polymerizable precursor solution. In steps 5 and 6, the positive and negative electrodes are processed independently. The negative electrode side also undergoes stepwise heating, but since the permeation treatment solution does not contain vinylene carbonate, a vinylene carbonate-rich interface modification layer will not form in the second heating stage. Step 7, stacking and assembly, is the same as in Example 1. Due to differences in the electrolyte formulations and polymerization processes of the two gels, the chemical composition and crosslinking density of the two gels at the interface are mismatched during stacking and fusion. Comparative Example 3 simultaneously changed the presence or absence of vinylene carbonate on the negative electrode side and the amount of crosslinking agent, aiming to comprehensively demonstrate the adverse effects of inconsistent gel composition on interface fusion. The comparison between Example 1 and Comparative Examples 1, 2, and 4 has independently demonstrated the necessity of the vinylene carbonate interface layer and homogeneous fusion.

[0053] Comparative Example 4 The difference from Example 1 is that after stacking and pressurizing in step 7, a porous polypropylene membrane with a thickness of 10 μm is inserted between the gel electrolyte layers of the positive and negative composite electrodes as an isolation layer before pressurization and encapsulation. The other steps are exactly the same as in Example 1. This comparative example illustrates that even if the gel electrolyte composition is the same, macroscopic physical interfacial impedance will occur if the stacked contact surfaces are physically isolated, preventing interdiffusion and fusion of chain segments.

[0054] Performance Tests and Results The solid-state lithium batteries assembled in Example 1 and Comparative Examples 1 to 4 were placed in a constant temperature chamber at 25°C for 12 hours before electrochemical performance testing was performed.

[0055] Initial electrochemical impedance spectroscopy (IOS) test: The initial interfacial impedance of each cell was measured according to the interfacial impedance determination method described above. .

[0056] Cyclic performance testing: The battery was charged at a constant current and constant voltage of 1 C to 4.25 V, with a cutoff current of 0.05 C. After resting for 5 minutes, it was discharged at a constant current of 1 C to 2.75 V, and this cycle was repeated. Electrochemical impedance spectroscopy was performed and recorded after every 200 charge-discharge cycles. Calculate the growth rate of the interface impedance after 1000 cycles.

[0057] High-potential float charge test: Fresh batteries were charged to 4.3 V at a constant current of 0.1 C, and then maintained at a constant potential of 4.3 V for 100 hours, with current changes monitored and recorded. After float charging, the batteries were allowed to stand for 2 hours before electrochemical impedance spectroscopy was performed, and the interfacial impedance growth rate was calculated based on the interfacial impedance values ​​before and after float charging.

[0058] The test results for each battery are summarized in Table 1.

[0059] Table 1. Comparison of interface impedance and growth rate between each embodiment and the comparative example.

[0060] As shown in Table 1, Example 1 significantly outperformed the comparative examples in terms of initial interfacial impedance, impedance stability after long cycling, and high-potential float charge tolerance. Comparative Example 1, lacking the introduction of vinylene carbonate, could not form an interfacial modification layer on the surface of the electrode active material particles. The ionic liquid components in the gel electrolyte underwent slow but continuous oxidation side reactions at the high charging potential of the positive electrode, leading to a continuous increase in interfacial impedance during cycling. Although Comparative Example 2 contained vinylene carbonate, the lack of a stepped heating program resulted in the vinylene carbonate being randomly distributed in the gel network via statistical copolymerization, failing to achieve enrichment and ordered film formation on the surface of the electrode active material particles. Therefore, its improvement in cycling stability was limited. In Comparative Example 3, the gel electrolyte formulations and crosslinking densities of the positive and negative composite electrodes differed. During stacking and pressurization, the polymer segments on both sides of the interface struggled to diffuse and entangle effectively. Furthermore, the discontinuity in chemical composition increased ion transport resistance, resulting in a significantly higher macroscopic interfacial impedance than Example 1, which became a preferential degradation region during cycling. In Comparative Example 4, although the gel electrolytes on both sides used the exact same formulation and process, the inserted polypropylene diaphragm prevented direct segment contact and fusion of the gel layers, forming a clear two-phase interface, resulting in a significant increase in interfacial impedance. This comparison further illustrates the necessity of removing the diaphragm and directly pressurizing and fusing the homogeneous gels on both sides in Example 1 to reduce interfacial impedance.

[0061] In summary, Example 1 introduces vinylene carbonate as an active diluent and sacrificial film-forming component into the precursor. Combined with a stepped temperature ramping program, vinylene carbonate preferentially participates in film formation on the surface of electrode active material particles to form an interface modification layer with continuously varying components. After preparing the positive and negative composite electrodes using the same precursor and polymerization process, they are directly fused under pressure. The synergistic effect at both the physical structure and chemical composition levels ultimately achieves low initial interface impedance and excellent interface stability of solid-state lithium batteries under long-term cycling and high-potential conditions.

[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. All equivalent substitutions, modifications, and improvements made within the principles of the technical solutions of the present invention should be included within the protection scope of the present invention. This invention encompasses any substitutions, modifications, equivalent methods, and solutions made within the spirit and scope of this invention. To provide the public with a thorough understanding of this invention, specific details are described in detail in the following preferred embodiments; however, those skilled in the art will fully understand the invention even without these details. Furthermore, to avoid unnecessary misunderstanding of the essence of this invention, well-known methods, processes, procedures, components, and circuits are not described in detail.

[0063] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for achieving integrated assembly of solid-state lithium batteries with low interfacial impedance using in-situ polymerized gel electrolyte, characterized in that, Includes the following steps: Step 1: Prepare the positive porous electrode and the negative porous electrode; Step 2: In an inert gas atmosphere, a polymerizable ionic liquid monomer, a crosslinking agent containing at least two olefin bonds, a lithium salt, and a thermal initiator are mixed to prepare a polymerizable precursor solution. Step 3: In an inert gas atmosphere, the polymerizable precursor solution and vinylene carbonate are mixed at a volume ratio of 5:1 to 10:1 to obtain a permeation treatment solution. Step 4: Completely immerse the positive porous electrode and the negative porous electrode in the permeation treatment solution, and maintain the immersion at a temperature of 25°C to 40°C for 30 minutes to 120 minutes to allow the permeation treatment solution to penetrate into the pores of the positive porous electrode and the negative porous electrode. Then, remove the electrodes and let them stand to drip off excess liquid from the surface to obtain a positive porous electrode and a negative porous electrode with the permeation treatment solution adsorbed on them. Step 5: In an inert gas atmosphere, the positive porous electrode and the negative porous electrode adsorbed with the permeation treatment liquid are placed in a sealed container and subjected to a stepped temperature in-situ polymerization treatment. The stepped temperature in-situ polymerization treatment includes a first heating stage, a second heating stage, and a third heating stage. The first heating stage includes heating from 25°C to 65°C at a heating rate of 1°C / min and holding at 65°C for 2 hours. The second heating stage includes heating from 65°C to 85°C at a heating rate of 0.5°C / min and holding at 85°C for 4 hours, so that the vinylene carbonate is enriched on the surface of the positive and negative active material particles and participates in the interfacial crosslinking reaction to form an interfacial modification layer. The third heating stage includes heating from 85°C to 100°C at a heating rate of 0.5°C / min and holding at 100°C for 2 hours. After natural cooling, an integrated positive composite electrode and an integrated negative composite electrode are obtained. Step 6: In an inert gas atmosphere, the gel electrolyte layer of the integrated positive electrode composite electrode and the gel electrolyte layer of the integrated negative electrode composite electrode are stacked face to face, a uniform pressure of 0.05 MPa to 0.2 MPa is applied, the pressure is maintained for 30 seconds to 120 seconds, and then vacuum encapsulation is performed to obtain a solid-state lithium battery.

2. The method for integrated assembly of a solid-state lithium battery with low interfacial impedance using in-situ polymerized gel electrolyte according to claim 1, characterized in that, In step 2, the polymerizable ionic liquid monomer is 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide salt, the crosslinking agent containing at least two olefin bonds is polyethylene glycol diacrylate, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide, and the thermal initiator is azobisisobutyronitrile; the molar ratio of the polymerizable ionic liquid monomer, the crosslinking agent containing at least two olefin bonds, the lithium salt, and the thermal initiator is 100:(2-10):(15-40):(0.5-3); the number average molecular weight of the polyethylene glycol diacrylate is 200 to 1000; the process of preparing the polymerizable precursor solution is completed at 25°C by magnetic stirring for 2 to 4 hours.

3. The method for integrated assembly of a solid-state lithium battery with low interfacial impedance using in-situ polymerized gel electrolyte according to claim 1, characterized in that, In step 3, the polymerizable precursor solution and vinylene carbonate are mixed in a glove box under an inert gas atmosphere, wherein the water content and oxygen content of the glove box are less than 0.1 ppm and less than 0.1 ppm respectively; the mixing is completed at 25°C by magnetic stirring for 0.5 to 1 hour to obtain a homogeneous permeation treatment solution; in the permeation treatment solution, vinylene carbonate simultaneously serves as a diluent to reduce the viscosity of the permeation treatment solution and as a sacrificial film-forming component that preferentially participates in film formation on the surface of the electrode active material particles in the second heating stage of step 5.

4. The method for integrated assembly of a solid-state lithium battery with low interfacial impedance using in-situ polymerized gel electrolyte according to claim 1, characterized in that, In step 4, the operation of completely immersing the positive and negative porous electrodes in the permeation treatment solution is carried out in a glove box protected by an inert gas atmosphere. The glove box has a water content of less than 0.1 ppm and an oxygen content of less than 0.1 ppm. All the interconnecting pores of the positive and negative porous electrodes are filled with the permeation treatment solution, so that the permeation treatment solution achieves molecular-level contact with the surfaces of the positive and negative active material particles. After the electrodes are removed, they are left to stand in a sealed container for 5 to 10 minutes to allow excess permeation treatment solution on the surface to drip off naturally.

5. The method for integrated assembly of a solid-state lithium battery with low interfacial impedance using in-situ polymerized gel electrolyte according to claim 1, characterized in that, In step 5, the positive porous electrode with the adsorbed permeation treatment liquid and the negative porous electrode with the adsorbed permeation treatment liquid are placed independently in a pressure-resistant sealed container, and argon gas is introduced into the pressure-resistant sealed container until the gauge pressure is 0.05 MPa to 0.1 MPa; the heating rate of the first heating stage is 1℃ / min, and the holding time at 65℃ is 2 hours; the heating rate of the second heating stage is 0.5℃ / min, and the holding time at 85℃ is 4 hours; the heating rate of the third heating stage is 0.5℃ / min, and the holding time at 100℃ is 2 hours; the natural cooling is to allow the container temperature to drop naturally to 25℃ after heating is stopped.

6. The method for integrated assembly of a solid-state lithium battery with low interfacial impedance using in-situ polymerized gel electrolyte according to claim 5, characterized in that, During the second heating stage, the vinylene carbonate is enriched on the surfaces of both the positive and negative electrode active material particles and participates in the interfacial cross-linking reaction, forming an interfacial modification layer with a thickness of 3 to 30 nanometers. X-ray photoelectron spectroscopy depth profiling shows that the characteristic signal intensity of the vinylene carbonate in the interfacial modification layer gradually decreases from the particle surface towards the gel electrolyte bulk, while the characteristic signal intensity of the ionic liquid monomer gradually increases, indicating that the chemical composition of the interfacial modification layer undergoes a continuous and gradual transition. The interfacial modification layer is connected to the polymer network backbone of the nascent gel electrolyte formed in the first heating stage through grafted chains and physical entanglement, without a clearly defined phase separation interface.

7. The method for integrated assembly of a solid-state lithium battery with low interfacial impedance using in-situ polymerized gel electrolyte according to claim 5, characterized in that, After the third heating stage, the content of residual vinylene carbonate monomer in the integrated positive electrode composite electrode and the integrated negative electrode composite electrode is less than 0.5 wt%, and the content of residual polymerizable ionic liquid monomer is less than 1 wt%; the gel electrolyte in the integrated positive electrode composite electrode and the integrated negative electrode composite electrode has an ionic conductivity of not less than 1×10⁻⁶. -3 The energy modulus of the gel electrolyte is S / cm, and the energy storage modulus of the gel electrolyte is between 0.1 MPa and 1 MPa.

8. The method for integrated assembly of a solid-state lithium battery with low interfacial impedance using in-situ polymerized gel electrolyte according to claim 1, characterized in that, In step 6, the gel electrolyte layer of the integrated positive electrode composite electrode and the gel electrolyte layer of the integrated negative electrode composite electrode are prepared using the same polymerizable precursor solution and polymerization process. During the application of a uniform pressure of 0.05 MPa to 0.2 MPa and holding the pressure for 30 to 120 seconds, the polymer chains at the interface of the two gel electrolyte layers undergo mutual diffusion and physical entanglement. The unreacted olefin bonds in the interface region further undergo covalent cross-linking under local chain segment movement, forming a continuous interface region where physical entanglement and local covalent cross-linking coexist. The ion transport impedance of the continuous interface region is not higher than 1.2 times the bulk ion transport impedance of the gel electrolyte body. The vacuum encapsulation uses an aluminum-plastic composite film with a sealing vacuum degree of -0.095 MPa to -0.08 MPa.

9. The method for integrated assembly of a solid-state lithium battery with low interfacial impedance using in-situ polymerized gel electrolyte according to claim 1, characterized in that, In step 1, the positive porous electrode is composed of positive active material powder, conductive additive powder, and polyvinylidene fluoride binder in a mass ratio of 92:4:4 to 96:2:2; the positive active material powder is an intercalated lithium transition metal oxide, and the conductive additive powder is conductive carbon black; the positive porous electrode is prepared by dispersing the positive active material powder, conductive additive powder, and polyvinylidene fluoride binder in N-methylpyrrolidone to obtain a positive electrode slurry, coating the positive electrode slurry onto an aluminum foil current collector with a coating thickness of 80 micrometers to 200 micrometers, and drying it at a temperature of 80°C to 120°C for 12 hours.

10. The method for integrated assembly of a solid-state lithium battery with low interfacial impedance using in-situ polymerized gel electrolyte according to claim 1, characterized in that, In step 1, the porous negative electrode is composed of graphite negative electrode active material powder, conductive additive powder, and composite aqueous binder in a mass ratio of 94:2:4 to 96:2:2; the composite aqueous binder is composed of styrene-butadiene rubber and sodium carboxymethyl cellulose in a mass ratio of 2:1 to 3:1; and the conductive additive powder is conductive carbon black. The porous negative electrode is prepared by dispersing the graphite negative electrode active material powder, conductive additive powder, and composite aqueous binder in deionized water to obtain a negative electrode slurry, coating the negative electrode slurry onto a copper foil current collector with a coating thickness of 60 micrometers to 150 micrometers, and drying it at a temperature of 80°C to 100°C for 12 hours.